Timing and Duration of High-Temperature Gold Mineralization and Spatially Associated Granitoid Magmatism at Chalice, Yilgarn Craton, Western Australia - Bucci, L.; McNaughton, Neal; Fletcher, Ian; Groves, D.; Kositcin, N.; Stein, H.; Hagemann, S. (Society of Economic Geologists Inc, 2004)
The Chalice gold deposit, in the Eastern Goldfields province, Yilgarn Craton, Western Australia, is located in a middle to upper amphibolite facies metamorphic domain and is hosted by a mafic-ultramafic rock sequence that has been locally intruded by four generations of monzogranite dikes. Two stages of gold mineralization,identified on the basis of crosscutting relationships, formed under broadly synpeak to postpeak metamorphicconditions. Main stage gold mineralization (95% of the resource) comprises foliation-parallel, quartz-albitediopside-titanite-garnet-gold veins and wall-rock replacement, both within locally developed asymmetric foldsin mafic amphibolite. Second stage gold mineralization (5% of the resource) is temporally associated with a second-generation monzogranite dike that cross cuts the folds and hence is younger than the Main event. It is representedby disseminated gold in the dike as well as by foliation-discordant quartz-gold, quartz-diopside-gold, actinolite-gold, and molybdenite-tellurobismuthite-gold veins. Gold is in textural equilibrium with the hydrothermal alteration assemblages in both mineralization stages and also with primary igneous phases (quartz and feldspar) in the monzogranite dike in the Second stage ore. Magmatic zircons and titanite from second and fourth generation monzogranite dikes and a monzogranite stock, as well as hydrothermal titanite and molybdenite in equilibrium with gold from hydrothermal alteration assemblages, allow dating of the important magmatic and hydrothermal events using the U-Pb and Re-Os isotope systems. Two gold events are identified. Main stage mineralization is coincident with asymmetric fold developmentat 2644 8 Ma (SHRIMP U-Pb on titanite), and Second stage mineralization (2621 10 Ma; Re-Os on molybdenite) is coeval, within the error of the isotopic ages, with the intrusion of the gold-mineralized second-generation monzogranite dike (2626 9 Ma; SHRIMP U-Pb on zircon). Ages of hydrothermal titanitein monzogranite dikes (2631 10 Ma, 2624 7 Ma, 2623 5 Ma, and 2619 6 Ma; SHRIMP U-Pb ages) indicate contemporaneous hydrothermal alteration, gold mineralization, and evolving magmatism during the Second stage event. A fourth generation, flat-lying pegmatite, which truncates all mine rock units, constrains the minimum age of mine-scale gold-bearing alteration and magmatism to 2622 13 Ma.The geologically constrained geochronologic data suggest that the Chalice gold deposit is a product of two independent gold events separated by up to 20 m.y., within an extended period of granitoid magmatism also extending over ~20 m.y. It demonstrates, for the first time in the extensively gold-mineralized Yilgarn craton, a clear interdependence and interplay between ongoing granitoid magmatism, deformation, hydrothermal alteration, and gold mineralization in amphibolite-hosted deposits. However, although integrated field and geochemical research establish a clear chronology of events, the controversy of contribution from magmatic and/or metamorphic fluids for the ore remains unresolved, because these events are broadly coeval within the resolution of the isotopic techniques.